1981
DOI: 10.1039/p19810001213
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of condensed tannins. Part 1. Stereoselective and stereospecific syntheses of optically pure 4-arylflavan-3-ols, and assessment of their absolute stereochemistry at C-4 by means of circular dichroism

Abstract: Stereoselective and also stereospecific condensation at C-4 of flavan-3,4-diols of known absolute configuration with phloroglucinol and resorcinol in acid medium proceeds at ambient temperatures with partial retention of configuration for 2,3-trans-isomers and with inversion for 2,3-cis-analogues. Circular dichroism spectra of the resultant 4-arylflavan-3-01s all exhibit multiple Cotton effects. The sign of high intensity Cotton effects to low wavelength, contributed by aryl chromophores at C-4, may almost inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 2 publications
7
78
0
Order By: Relevance
“…In addition, the 4b → 8-linkage and thus the R-configuration at C-4(C) was confirmed by the strong positive Cotton effect observed between 220 and 230 nm, and 280 nm in the CD spectrum. [22][23][24][25][26][27] The missing NOE effect between H-2(C) and H-4(C) strongly supported the proposed 4b orientation of the interflavanoid bond. The high-amplitude positive Cotton effect was caused by the phenylpropanoid substituent with an S-configuration at C-7".…”
Section: Structure Of Phenylpropanoid Substituted Flavan-3-olsmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, the 4b → 8-linkage and thus the R-configuration at C-4(C) was confirmed by the strong positive Cotton effect observed between 220 and 230 nm, and 280 nm in the CD spectrum. [22][23][24][25][26][27] The missing NOE effect between H-2(C) and H-4(C) strongly supported the proposed 4b orientation of the interflavanoid bond. The high-amplitude positive Cotton effect was caused by the phenylpropanoid substituent with an S-configuration at C-7".…”
Section: Structure Of Phenylpropanoid Substituted Flavan-3-olsmentioning
confidence: 87%
“…In general, the 4S-linkage between two flavan units produces negative Cotton effects at 220-240 and 275 nm in the CD spectra. [22][23][24][25][26][27] Such negative Cotton effects can be observed in the spectrum of compound 9a, in addition to a positive Cotton effect at 255 nm. The latter effect is (probably) due to the S-configuration of the phenylpropanoid substituent.…”
Section: Structure Of Phenylpropanoid Substituted Flavan-3-olsmentioning
confidence: 99%
“…These degradation products were identified by co-chromatography in comparison with authentic compounds (Qa'dan et al, 2006). The high amplitude positive cotton effect at low wavelengths (210-240 nm) in the CD spectrum of compound 7a confirmed the absolute configuration of the extender units as 4R (Barrett et al, 1979;Botha et al, 1981). In conjunction with the optical rotation [α] 20 = +107.6° (c = 1.65, MeOH), compound 7 was characterized as epigallocatechin-(4β→8)-epigallocatechin-(4β→8)-catechin.…”
mentioning
confidence: 96%
“…Finally, the absolute stereochemistry of 1 was elucidated by circular dichroism (CD) spectrum, which showed a negative Cotton effect in the short wavelength region (Δε −37.54 at 214 nm), indicating that the orientation of the 4-position in the flavan-3-ol unit is S configuration. 21,[44][45][46][47] This evidence indicated that the absolute configuration of 1 was determined to be 2R, 3S, 4S, 3″S, and 4″S orientations. Consequently, the absolute stereostructure of 1 was determined to be as shown.…”
mentioning
confidence: 96%